2017
DOI: 10.1177/0891243217732320
|View full text |Cite
|
Sign up to set email alerts
|

Motherhood, Employment, and the Dynamics of Women’s Gender Attitudes

Abstract: This article presents an investigation of the dynamics of women's gender attitudes from the perspective of women's conflicting employment and childrearing responsibilities. It examines the independent and joint effects of motherhood and employment on gender attitudes using combined data from the British Household Panel Survey and the Understanding Society panel study. The results of fixed effects models show no evidence supporting a direct influence of either motherhood or employment on women's attitudes towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 47 publications
1
33
0
8
Order By: Relevance
“…For example, South and Spitze (1994) found that among both women and men, marriage was associated with more housework time. Marriage is also associated with more traditional gender attitudes (Zhou, 2017). On the other hand, Baxter, Hewitt, and Haynes (2008) found that the effects are applicable to women but not to men.…”
Section: Theoretical Expectationsmentioning
confidence: 96%
“…For example, South and Spitze (1994) found that among both women and men, marriage was associated with more housework time. Marriage is also associated with more traditional gender attitudes (Zhou, 2017). On the other hand, Baxter, Hewitt, and Haynes (2008) found that the effects are applicable to women but not to men.…”
Section: Theoretical Expectationsmentioning
confidence: 96%
“…Moreover, life-course transitions such as the transition from being single to being married are expected to influence the association between education and participation in housework. The research in the western countries shows that women increase their housework participation regardless of their educational level when they marry and have children (Baxter et al, 2008;Gupta, 1999;Zhou, 2017). In Japan, we expect similar effects on each transition (marriage and parenthood):…”
Section: Current Studymentioning
confidence: 80%
“…On the other hand, the life-course perspective emphasizes that the effects of economic resources on housework participation might vary depending on the life-course stage (Baxter, Hewitt, & Haynes, 2008;Coltrane & Ishii-kuntz, 1992;He & Zhou, 2018;Kan & Gershuny, 2010;Nitsche & Grunow, 2016;Zhou, 2016Zhou, , 2017Zhou, Wu, & He, 2017). However, many assumptions in the life-course analysis of housework participation, especially those derived from the processes of gender socialization and the effects of life transitions, remain unquestioned and continue to be applied directly to the cultural contexts other than in the global north.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to recieve a variety of information and knowledge is obtained from a program of functional literacy that is done consciously and can be planned. It also implicitly implies that the significance of a woman's identity as a worker is undermined when women hold the primary responsibility for child care (Zhou, 2017).…”
Section: Resultsmentioning
confidence: 99%